2011
DOI: 10.5194/acp-11-6083-2011
|View full text |Cite
|
Sign up to set email alerts
|

Application of SCIAMACHY and MOPITT CO total column measurements to evaluate model results over biomass burning regions and Eastern China

Abstract: Abstract. We developed a new CO vertical column density product from near IR observations of the SCIAMACHY instrument onboard ENVISAT. For the correction of a temporally and spatially variable offset of the CO vertical column densities we apply a normalisation procedure based on coincident MOPITT (version 4) observations over the oceans. The resulting normalised SCIAMACHY CO data is well suited for the investigation of the CO distribution over continents, where important emission sources are located. We use on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 68 publications
7
40
3
Order By: Relevance
“…Additionally, the biomass burning emissions of BC and POM in the inventory (2.12 and 18.45 Tg yr −1 , respectively) may be underestimated, as they are lower than what is suggested in the literature (3.1 and 34.7 Tg yr −1 , respectively, Dentener et al, 2006). The underestimations of the biomass burning sources has been noticed for the same simulation also for other emitted compounds (CO, Liu et al, 2011) when compared to satellite observations. The underestimation could possibly produce a bias in the AOD estimates by the model, which results in an underestimation of AOD when compared with MODIS and MISR, as observed e.g.…”
Section: Comparison With Satellite Observationssupporting
confidence: 54%
“…Additionally, the biomass burning emissions of BC and POM in the inventory (2.12 and 18.45 Tg yr −1 , respectively) may be underestimated, as they are lower than what is suggested in the literature (3.1 and 34.7 Tg yr −1 , respectively, Dentener et al, 2006). The underestimations of the biomass burning sources has been noticed for the same simulation also for other emitted compounds (CO, Liu et al, 2011) when compared to satellite observations. The underestimation could possibly produce a bias in the AOD estimates by the model, which results in an underestimation of AOD when compared with MODIS and MISR, as observed e.g.…”
Section: Comparison With Satellite Observationssupporting
confidence: 54%
“…In recent publications of Liu et al (2011), satellite measurements and model simulations showed that monthly mean of CO vertical column density had a maximum in winter and minimum in summer in the eastern area of China Diurnal variation can be obtained by analysing data on a daily timescale. 24 October 2014 is selected because the data sampled on this clear-sky day cover long daylight hours and are continuous.…”
Section: Variation Of Xco 2 and Xcomentioning
confidence: 99%
“…The oxidation of CO also leads to the formation of carbon dioxide (CO 2 ) and tropospheric ozone (O 3 ) (Crutzen and Gidel, 1983;Fishman and Crutzen, 1978;Burrows et al, 1995). Because of its moderately long lifetime (weeks to months) and inhomogeneous distribution in the troposphere, CO is an ideal tracer for monitoring the air pollution sources and transports (Cicerone, 1988;Logan et al, 1981;Shindell et al, 2006;Lelieveld et al, 2001;Hoor et al, 2005;Edwards et al, 2004Edwards et al, , 2006Pan et al, 1995;Worden et al, 2013a;Liu et al, 2011Liu et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%